2020
DOI: 10.1111/jcal.12456
|View full text |Cite
|
Sign up to set email alerts
|

A mobile game as a support tool for children with severe difficulties in reading and spelling

Abstract: We used a randomized controlled trial to investigate if a mobile game, GraphoLearn (GL), could effectively support the learning of first graders (N = 70), who have severe difficulties in reading and spelling. We studied the effects of two versions of the game: GL Reading, which focused on training letter-sound correspondence and word reading; and GL Spelling, which included additional training in phonological skills and spelling. During the spring of first grade, the children trained with tablet computers whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 50 publications
(86 reference statements)
1
11
0
Order By: Relevance
“…These findings align with those of previous longitudinal studies (Pajares and Graham, 1999;Phan, 2012b), in which the level of SE was found to predict later math performance. Similar findings were also made in reading that showed that children with high SE benefit more from skill training than those with low SE (Ronimus et al, 2020). As children with high SE are suggested to put forth more effort and persistence in learning situations and to choose more learning activities (Bandura, 1986(Bandura, , 1997, it is not surprising that they also improved more, as was shown in our study.…”
Section: Differences In the Level And Changes In Se And Calculation Fluency Improvement During Interventionssupporting
confidence: 90%
“…These findings align with those of previous longitudinal studies (Pajares and Graham, 1999;Phan, 2012b), in which the level of SE was found to predict later math performance. Similar findings were also made in reading that showed that children with high SE benefit more from skill training than those with low SE (Ronimus et al, 2020). As children with high SE are suggested to put forth more effort and persistence in learning situations and to choose more learning activities (Bandura, 1986(Bandura, , 1997, it is not surprising that they also improved more, as was shown in our study.…”
Section: Differences In the Level And Changes In Se And Calculation Fluency Improvement During Interventionssupporting
confidence: 90%
“…In addition, games, digital games, educational games, and video games, together, are the second most used set of author keywords. It can be inferred from this finding that the term "serious game" has been used in the majority of articles, especially in recent years (Bang et al, 2019;Faria et al, 2019;García-Redondo et al, 2019;Jaramillo-Alcázar et al, 2020;Lievense et al, 2019;Ronimus et al, 2020;Tang et al, 2019). Based on the bibliometric results, disability and rehabilitation are also among the most used author keywords.…”
Section: Discussionmentioning
confidence: 96%
“…High level of self-efficacy is revealed to contribute to learners' growth in reading (Capara et al, 2008). Several studies have reported the higher self-efficacy beliefs, the better results in developing reading comprehension (Bağcı, 2019;Barkley, 2006;Cho et al, 2015;Forzani et al, 2021;Hedges & Gable, 2016;McLean & Poulshock, 2018;Peura et al, 2019;Ronimus et al, 2020;Soland & Sandilos, 2020;Tremblay & Gardner, 1995;Unrau et al, 2018). Basically, attitudes towards reading could influence reading self-efficacy of an individual; for instance, individuals who enjoy reading are shown to have higher levels of reading self-efficacy in comparison to the ones not enjoying reading (Burrows, 2012;Carroll & Fox, 2017).…”
Section: Introductionmentioning
confidence: 99%